Inverse design of 2-D subsonic ducts using flexible string algorithm - Nili-Ahmadabadi, Mahdi; Durali, Mohammad; Hajilouy-Benisi, Ali; Ghadak, Farhad (Inverse problems in science and engineering, 2009)
The duct inverse design in fluid flow problems usually involves finding the wall shape associated with a prescribed distribution of wall pressure or velocity. In this investigation, an iterative inverse design method for 2-D subsonic ducts is presented. In the proposed method, the duct walls shape is changed under a novel algorithm based on the deformation of a virtual flexible string in flow. The deformation of the string due to the local flow conditions resulting from changes in wall geometry is observed until the target shape satisfying the prescribed wall's pressure distribution is reached. The flow field at each step is analysed using Euler equations and the advection upstream splitting method method. Some validation test cases and a design example are presented here which show the robustness and flexibility of the method in handling complex geometries. The method is a physical and quick converging approach and can efficiently utilize commercial flow analysis software.